Ultrasonic-assisted extraction, anti-biofilm activity, and mechanism of action of Ku Shen (Sophorae Flavescentis Radix) extracts against Vibrio parahaemolyticus - Zhao, Yanan; Guo, Siya; Li, Shuge; Ye, Enjun; Wang, Wenfang; Wang, Tong; Wen, Ying; Guo, Lei (Frontiers in Microbiology, 2024)
The objective of this study is to optimize the ultrasonic-assisted extraction process of Ku Shen (Sophorae Flavescentis Radix) extracts (KSE) against Vibrio parahaemolyticus and explore their anti-biofilm activity and mechanism of action. The ultrasonic-assisted extraction process of KSE optimized by single factor experiment, Box–Behnken design and response surface methodology was as follows: 93% ethanol as solvent, liquid/material ratio of 30 mL/g, ultrasonic power of 500 W, extraction temperature of 80°C and time of 30 min. Under these conditions, the diameter of inhibition circle of KSE was 15.60 ± 0.17 mm, which had no significant difference with the predicted value. The yield of dried KSE is 32.32 ± 0.57% and the content of total flavonoids in KSE was 57.02 ± 5.54%. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of KSE against V. parahaemolyticus were 0.25 and 0.5 mg/mL, respectively. Crystal violet staining, Congo red plate, spectrophotometry, CCK-8 and scanning electron microscopy were used to investigate the activity and mechanism of action of KSE against V. parahaemolyticus biofilm. The results showed that the sub-MIC of KSE could significantly inhibit biofilm formation, reduce the synthesis of polysaccharide intercellular adhesin (PIA) and the secretion of extracellular DNA. In addition, the inhibition rate of biofilm formation and clearance rate of mature biofilm of 1.0 mg/mL KSE were 85.32 and 74.04%, and the reduction rate of metabolic activity of developing and mature biofilm were 77.98 and 74.46%, respectively. These results were confirmed by visual images obtained by scanning electron microscopy. Therefore, KSE has the potential to further isolate the anti-biofilm agent and evaluate it for the preservation process of aquatic products.